1987
DOI: 10.1002/path.1711510412
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal circulatory disturbance by microthrombosis as a cause of endotoxin‐induced hepatic injury

Abstract: The present study was undertaken in rats to examine the significance of sinusoidal circulatory disturbance by microthrombosis in the pathogenesis of hepatic damage and dysfunction due to endotoxin. Administration of endotoxin induced fibrin deposits and infiltration of polymorphonuclear leukocytes in the sinusoids, focal random coagulative hepatocellular necrosis and elevation of serum transaminase activities. When heparin was given simultaneously with endotoxin, the formation of fibrin thrombus in the sinusoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 16 publications
0
26
0
1
Order By: Relevance
“…In rats, infusion of thrombin into the por-24]. In the rat, circulating plasma fibrinogen concentra-tal vein induces damage similar to that observed after tion falls dramatically after intravenous injection of administration of LPS [13], and antithrombin III atten-LPS [2,8], and there is morphologic evidence of fibrin uates the effects of LPS [28]. The observations that deposition within the liver sinusoids [12,25].…”
Section: Figmentioning
confidence: 94%
See 1 more Smart Citation
“…In rats, infusion of thrombin into the por-24]. In the rat, circulating plasma fibrinogen concentra-tal vein induces damage similar to that observed after tion falls dramatically after intravenous injection of administration of LPS [13], and antithrombin III atten-LPS [2,8], and there is morphologic evidence of fibrin uates the effects of LPS [28]. The observations that deposition within the liver sinusoids [12,25].…”
Section: Figmentioning
confidence: 94%
“…Because one of the LPS-induced changes is results indicate that thrombin is a critical and distal deposition of fibrin in the microvasculature of the liver mediator of LPS-induced liver damage and contributes [12], it has been hypothesized that occlusion of the microto hepatocellular injury through a mechanism that is circulation by insoluble fibrin clots and consequent ischindependent of clot formation. Furthermore, inflamma-emia are responsible for the liver necrosis [13,14]. Recent tory events triggered by LPS exposure are a prerequisite results, however, have raised doubts about this theory.…”
mentioning
confidence: 97%
“…Studies have shown that endotoxemia is a common complication of multi organ failure (MOF) and ET are believed to be strongly associated with the pathogenesis of acute liver damage in a variety of experimental models [29,30]. Therefore, the evaluation of clinical liver function tests can provide information about the effect of hemoperfusion on sepsis treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Liver injury caused by in vivo LPS administration is thought partly because extremely swollen Kupffer cells, platelet aggregation, and granulocytes obstruct the sinusoids, and result in liver tissue damage [Shibayama., 1987;Van et al, 1988]. By the light microscopy and electron microscopy findings, the hypothesis has been established on the basis of these structural analysis.…”
Section: Discussionmentioning
confidence: 99%